Frictional Stability of Metamorphic Epidote in Granitoid Faults Under Hydrothermal Conditions and Implications for Injection‐Induced Seismicity. Issue 3 (16th March 2022) - An, Mengke; Zhang, Fengshou; Min, Ki‐Bok; Elsworth, Derek; He, Changrong; Zhao, Luanxiao
Abstract: The presence of metamorphic epidote on faults has been implicated in the transition from stable to unstable slip and the nucleation of earthquakes. We present structured laboratory observations of mixed epidote and simulated Pohang granodiorite (analogous to the EGS‐enhanced geothermal system site) gouges to evaluate the impact of heterogeneity and contiguity of epidote‐patch structure on frictional instability. Experiments are at a confining pressure of 110 MPa, pore fluid pressures of 42–63 MPa, temperatures 100–250°C and epidote percentages of 0–100 vol.%. The simulated Pohang granodiorite gouge is frictionally strong (friction coefficient ∼0.71) but transits from velocity‐strengthening to velocity‐weakening at temperatures >150°C. This velocity‐weakening effect is amplified in approximate proportion to increasing epidote content. Modes of epidote precipitation likely control the size and contiguity of the epidote‐only patches and this in turn changes the response of 50:50 epidote‐granodiorite mixed gouges for different geometric configurations. However, 50:50 epidote‐granodiorite mixtures that are variously homogeneously mixed, encapsulated and checkerboarded in their structures are insensitive to their geometries – all reflect the high frictional strength and strong velocity‐weakening response of 100:0 pure epidote. This suggests that the epidote present as thin coatings on fractures/faults can enhance velocity‐weakening behavior, independent of individual patch size and can thereby support the potential seismic reactivation of faults. Considering the frictional and stability properties of epidote at conditions typical of shallow depths, the presence of low‐grade metamorphism exerts a potentially important control on fault stability in granitoids with relevance as a marker mineral for susceptibility to injection‐induced seismicity. Plain Language Summary: Epidote is a common mineral on fractures/faults in granites that results from both the natural and forced circulation of hot fluids – for example, in geothermal reservoirs. Its presence, even in trace quantities and as a film on fractures can impact the ability of faults to slip either stably or unstably – the latter generating earthquakes. We conduct shear experiments on simulated faults of powdered granodiorite gouge containing varying percentages and structures of epidote through pure epidote and at varying temperatures and pressures representative of geothermal reservoirs. The powdered granodiorite and epidote gouges show similar and high frictional strengths but the addition of epidote results in unstable slip and the potential for seismicity. Increasing epidote proportion amplifies the weakening until 50:50 mixtures that behave as unstably as pure epidote – regardless of the epidote‐granite structure. This suggests that even trace amounts of epidote in thin films may be effective in destabilizing faults – with implications for the control of fault instability and earthquake triggering in geothermal reservoirs. Key Points: Epidote gouge is more v‐weakening than simulated gouge derived from the Pohang granite host above a transition T of ∼150°C Homogeneous and structured 50:50 mixtures of epidote:granodiorite show v‐weakening similar to epidote and are insensitive to structure Trace percentages of epidote present as thin coatings and even at small patch sizes are a potential factor controlling fault instability